Política, memória e cidade: As comemorações do III Centenário de Fundação da Capital Maranhense pelos Franceses em 1912 - SOUSA, Wendell Emmanuel Brito de (2016)
The present work has as an objective an analysis of the commemorations of the III Centenary of foundation of Saint Louis by the French as policies of memory. Following the indications of the celebrations of 1912, we perceive a conception of a city, where time and space are in harmony with each other, organize ideas and images about the city and, consequently, those who inhabit it. The sentimentalist contract instituted by these rituals, between the practices of incorporation and inscription (repertoire and archive); Constitutes an important laboratory for the problematization of the past, that is, how it was perceived, reconstructed, invented, forgotten and erased. Thus, one understands the selective character of these past evocations by revealing the rite as a symbolic product of social communion, but as a symbolic practice organized by groups and institutions, whose product would be the result of the articulation between present and past. In this sense, my thesis is the celebrations of the tricentennial was a socio-symbolic investment in images of the city that were close to the republican ideology of the political center of the country. Therefore, the investigation of the context of these evocations having the First Republic as a background was of paramount importance for the understanding of ritualizations. However, for the understanding of the celebrations of 1912 we invested an analysis about the principal civic rituals of the capital and its relation with time and space. A period where the conceptions of city, time and Republic begin to interfere in the civic repertoire: characters, dates and plot. A time in transfiguration, especially through the memory policies of the Luiz Domingues government.